Mesure et contrôle des propriétés de quelques eaux souterraines de l’agglomération d’Ouled Driss, Algérie - KHALDI, F; SMATI, H; GRARA, N; SMATI, N; MAIZI, N; BOUKEHILI, K; GHEID, A. (My University, 2018)
Measuring and controlling groundwater properties in Ouled Driss, Algeria Ain Nechema, Ain Souda, Ain Ras Oued, and Ain Maa Bared are important sources of drinking water for the inhabitants of Ouled Driss (Souk Ahras Province, in northeastern Algeria). This article is a qualitative and quantitative study of the physicochemical and bacteriological properties of the water, based on Algerian potability standards and the regulations in force, intended to ensure consumers’ health and well-being. The results of the physicochemical analysis showed that these waters are mineralized with a high content of bicarbonate and calcium, compared with other ions. The results meet Algerian drinking water standards, except for their elevated levels of lead and sodium. The results of the bacteriological analysis showed the presence of several fecal contamination indicators, including total coliforms, fecal coliforms, and fecal streptococci. Several sources of pollution are the cause of this degradation in water quality: waste discharge from the urban area close to the springs and agricultural activities such as cattle breeding